Estimación de áreas y volúmenes requeridos para el diseño y construcción de un relleno sanitario manual para la ciudad de Pinto Recodo - Pinedo Gonzales, Rolin (2010)
This thesis seeks to improve the service of disposal of municipal salid waste in the town of Pinto Recodo, in this sense it is filing a motion for areas and volumes required for the Design and Construction of a Manual Sanitary Landfill the town of Pinto Recodo which would permit the implementation of the project a proper disposal system consistent with the requirements of sanitary and environmental regulations of the country. lt is important to mention that the municipal authority must turn all these into account local environmental policy guidelines, and enable a better quality of life for all people in the district that has the right to enjoy a good public cleaning service. We must take into account that not only should be the priority Disposal phase if it is necessary to view the tapie of Awareness, Environmental Awareness and Training regarding the issue of public sanitation, is rightfully due them from generating sources In other words, the waste management must begin in the homes of each of the users of the Service. Also on duty the authority must provide the necessary logistics and budgets to optimize the service, in this sense this work 1 provide technical information that would permit the Design and Construction of a Manual Sanitary Landfill for the City of Pinto Bend from the environmental viewpoint and adequate sanitation. All the efforts that our authorities can channel in regard to municipal waste management is its importance to aspire to be regarded as a cultured city and majar tourist especially should be included in the regional tourism calendar as a potential tourist attraction and why not say that Pinto Recodo be regarded as a national tourist destination